ON SOLUTIONS OF LOCAL FRACTIONAL SCHRODINGER EQUATION - Yilmazer, Resat; Demirel, Neslihan S. (Vinca Inst Nuclear Sci, 2019)
In this study, we obtain the solution of a local fractional Schrodinger equation. The solution is obtained by the implementation of the Laplace transform and Fourier transform in closed form in terms of the Mittag-Leffler function.
Keywords: local fractional calculus; Laplace transforms; Fourier transform; Schrodinger equations